The Effectiveness of Audio-Visual Media on Primary School Students' Listening Skills: A Systematic Literature Review - Erni Yulia Ningsih; Yasinta Mahendra; Irawan Suprapto (Berkala Ilmiah Pendidikan, 2026)
Listening skills constitute a fundamental competency that elementary school students must master, as they provide the foundation for the development of other language skills. However, many students experience difficulties in acquiring listening proficiency due to less engaging instructional methods and challenges in sustaining attention. This study aims to analyze the effectiveness of audio-visual media in enhancing students' listening skills, particularly in content comprehension, inferential reasoning, and active participation and learning engagement. The study employed a Systematic Literature Review (SLR) methodology by identifying and examining relevant articles indexed in the Google Scholar database published between 2021 and 2025. Based on rigorous inclusion criteria, ten primary articles were selected for in-depth analysis. The findings indicate an increasing trend in publications on the use of audio-visual media, reaching a peak in 2025. The reviewed studies consistently demonstrate that integrating audio-visual media significantly improves elementary students' listening skills. This instructional medium facilitates more engaging, contextualized, and interactive learning experiences, thereby enhancing students' comprehension and participation. Accordingly, the innovative use of audio-visual media represents an effective pedagogical strategy for strengthening listening skills in elementary education.